Pengembangan Tutorial Edmodo Untuk Tenaga Pengajar - Luvita Maymadya (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
Based on observations of the teaching staff at SMAN 1 Ponggok, Kab. Blitar can be seen that teachers are still unable to build learning by utilizing existing technology, namely computers and the internet. So that the learning outcomes are less than optimal. Therefore, it is necessary to develop Edmodo Tutorial for Teachers which contains tutorials on the use and use of Edmodo in learning so that teachers can use it to solve these problems. The development model used in the development of Edmodo's tutorial is the ADDIE (2003) model. The ADDIE model is a simplified general learning system design model. The ADDIE development model development procedure includes Analysis, Design, Development, Implementation, and Evaluation. However, the developer only uses step three. The result of this development is a product in the form of a CD containing edmodo tutorials for teaching staff and guidance on the use of edmodo in learning, along with a manual for its use. To determine the validity level of the Edmodo tutorial, trials were carried out on material experts, media experts and potential users, namely the teaching staff. Overall, it can be concluded that the product that has been developed, in the form of a CD containing Edmodo Tutorial, is appropriate and valid for use as a learning resource. Although the small group and field trials the results were not as good as the trials from experts.